2003
DOI: 10.1021/om034053b
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Highly Electrophilic Binuclear Cations. 3. Reactivity of [W25-C5H5)2(μ-CO)(CO)2(μ-Ph2PCH2PPh2)][B{3,5-C6H3(CF3)2}4]2toward Small Donor Molecules

Abstract: Reaction of the unsaturated tricarbonyl complex [W 2 Cp 2 (µ-CO)(CO) 2 (µ-dppm)](BAr′ 4 ) 2 with HSPh leads to the thiolate-bridged complex [W 2 Cp 2 (µ-SPh)(µ-CO)(CO) 2 (µ-dppm)](BAr′ 4 ), which is obtained as a mixture of two isomers. This reaction proceeds faster in the presence of a base (1,8-diazabicyclo[5.4.0]undec-7-ene, DBU), as expected. The title compound also reacts at room temperature with stoichiometric amounts of phosphines HPRwhich display a trans relative geometry of their phosphide and diphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
3
14
1
Order By: Relevance
“…In contrast, the very minor isomer trans-3 has presumably the same geometry as compound 2, since its characteristic methyne resonance displays also very low P-H couplings (2 Hz). Interestingly, the ditungsten analogue of compound 2 was found to exist in solution as a roughly equimolar mixture of two isomers, these having spectroscopic properties resembling respectively those of 2 and 3 [6]. In particular, the P-H couplings of the methyne proton were found to be 1.5 and 1.5 Hz for one isomer, and 12 and 10 Hz for the other one.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, the very minor isomer trans-3 has presumably the same geometry as compound 2, since its characteristic methyne resonance displays also very low P-H couplings (2 Hz). Interestingly, the ditungsten analogue of compound 2 was found to exist in solution as a roughly equimolar mixture of two isomers, these having spectroscopic properties resembling respectively those of 2 and 3 [6]. In particular, the P-H couplings of the methyne proton were found to be 1.5 and 1.5 Hz for one isomer, and 12 and 10 Hz for the other one.…”
Section: Resultsmentioning
confidence: 97%
“…We then turned our attention to the oxidation reactions of compounds 1, since these could lead to dipositive and unsaturated cations able to activate the alkyne ligand with respect to either deprotonation or other rearrangements. We have previously shown that the presence of multiple metal-metal bonds combined with high positive charges at binuclear transition-metal complexes enhances the Lewis acidity of the dinuclear centre and promotes novel transformations of interest [4][5][6]. In this paper we report our results on the oxidation reactions of radicals 1a,b with [FeCp 2 ]X [X = BF 4 and BAr 0 4 ] and some reactivity studies of the resulting dipositive cations.…”
Section: Introductionmentioning
confidence: 94%
“…We have shown previously that bridging hydride ligands in related dipositive ions can exhibit quite deshielded 1 H NMR resonances (d H ca. 4 ppm in the [W 2 Cp 2 (m-H)(m-PRR 0 )(CO) 2 (m-Ph 2 PCH 2 PPh 2 )] 2þ cations [8]), thus facilitating its masking with other resonances in the spectrum. Besides this, the strong deshielding of the hydroxyl resonance of 4 is neither unexpected for a dipositive cation (cf.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, we have shown previously that the resonance of the bridging hydride in the 32-electron cations [W 2 Cp 2 (μ-H)­(μ-PR 2 )­(μ-Ph 2 PCH 2 PPh 2 )­(CO) 2 ] 2+ (PR 2 = PPh 2 , PHCy) is displaced from ca. −5 to + 3 ppm by just exchanging the relative positions of the PR 2 and H ligands …”
Section: Resultsmentioning
confidence: 99%